Przegląd naukowy inżynieria i kształtowanie środowiska - Szkoła Główna Gospodarstwa Wiejskiego w Warszawie. Wydział Inżynierii i Kształtowania Środowiska; Szkoła Główna Gospodarstwa Wiejskiego w Warszawie. Wydział Budownictwa i Inżynierii Środowiska (Wydawnictwo SGGW, 2001)
Covers broad area of knowledge and practice on fields such as: sustainable development, landscaping of non-urbanized lands, environmental engineering, construction projects engineering land management, protection and land reclamation, environmental impact of investments, ecology, hydrology and water management, ground-water monitoring and restoration, geotechnical engineering, meteorology and connecting subjects.
Keywords: Environmental engineering : Periodicals; Civil engineering : Periodicals; Civil engineering; Environmental engineering